Integrated application of meat waste-derived organic fertilizer and chemical fertilizer in sugarcane cultivation - Aselefech Sorsa Wotango; Feredegn Dagnaw; Mulatu Kassie Birhanu; Asnake Waltenigus Ewnetu; Tadesse Negi; Mesfin Tafesse Gemeda; Getachew Adam Workneh (PLoS ONE, 2026)
Slaughterhouse waste is a major source of environmental pollution. However, its rich organic content holds considerable potential for enhancing soil fertility. Herein, slaughterhouses meat waste was used to produce organic fertilizer (OF), and its effect on sugarcane growth, productivity and soil fertility were evaluated. The decomposition of the collected meat waste was carried out in a controlled fermentation pit. Initially, the sample was treated by sulfuric acid (H 2 SO 4 ), followed by the addition of potassium hydroxide (KOH) and dipotassium phosphate (K 2 HPO 4 ). The pH of the medium was then adjusted to neutral conditions, after that a bacterial inoculum was introduced to facilitate further biodegradation of the solid waste. The prepared organic fertilizer was characterized for its chemical compositions, physicochemical properties and microbial diversity. The chemical compositions analyses revealed that potentially toxic elements such as mercury (Hg), lead (Pb), cadmium (Cd) and arsenic (As) were detected at concentration of <0.002 mg/kg, 0.411 mg/kg, 0.004 mg/kg and 0.095 mg/kg, respectively, indicating their levels in the fertilizer were very low. The total organic carbon content was determined to be 13.90% that is significantly higher than that of most soil, where organic carbon levels typically fall below 2%. MALDI-TOF (Matrix-Assisted Laser Desorption/Ionization Time-of-Flight) mass spectrometry was used to identify culturable bacterial isolates obtained from the fermented organic fertilizer prior to soil application. A total of 20 morphological distinct isolates were analyzed, of which Lysinibacillus sphaericus was the most frequently detected species, followed by Bacillus simplex, Bacillus cereus, Kocuria varians, and Microascus sp. Identification was accepted based on MALDI-TOF score thresholds (≥2.0 species-level and 1.7–1.99 for genus level identification). Lysinibacillus sphaericus aids nitrogen-fixation, plant growth, and decomposing organic matter, all of which enhance soil fertility and plant health. Additionally, other species such as Bacillus simplex, Bacillus cereus, Kocuria varians , and Microascuswere contribute to phosphate solubilization and pathogen suppression. The organic ferilizer was tested alone and in combination with the conventional chemical fertilizer in a pot experiment for sugarcane. The results showed that applying 5 tonnes ha -1 of organic fertilizer together with 50% of the recommended chemical fertilizer performed comparable to that of 100% recommended chemical fertilizer alone. In addition, combined organic fertilizer and recommended chemical fertilizer resulted in a significantly higher juice phosphate content compared to the sole application of 100% recommended chemical fertilizer, likely due to the contribution of the organic fertilizer. This finding suggests that halving chemical fertilizer use by supplementing with organic alternatives could offer environmental benefits while maintaining productivity.